A successful 3D core-collapse supernova explosion model. Issue 1 (24th September 2018) - Vartanyan, David; Burrows, Adam; Radice, David; Skinner, M Aaron; Dolence, Joshua
Abstract: In this paper, we present the results of our three-dimensional, multigroup, multineutrino-species radiation/hydrodynamic simulation using the state-of-the-art code fornax of the terminal dynamics of the core of a non-rotating 16 M⊙ stellar progenitor. The calculation incorporates redistribution by inelastic scattering, a correction for the effect of many-body interactions on the neutrino–nucleon scattering rates, approximate general relativity (including the effects of gravitational redshifts), velocity-dependent frequency advection, and an implementation of initial perturbations in the progenitor core. The model explodes within ∼100 ms of bounce (near when the silicon–oxygen interface is accreted through the temporarily stalled shock) and by the end of the simulation (here, ∼677 ms after bounce) is accumulating explosion energy at a rate of ∼2.5 × 10 50 erg s −1 . The supernova explodes with an asymmetrical multiplume structure, with one hemisphere predominating. The gravitational mass of the residual proto-neutron star at ∼677 ms is ∼1.42 M⊙ . Even at the end of the simulation, explosion in most of the solid angle is accompanied by some accretion in an annular region at the wasp-like waist of the debris field. The ejecta electron fraction ( Ye ) is distributed between ∼0.48 and ∼0.56, with most of the ejecta mass proton-rich. This may have implications for supernova nucleosynthesis, and could have a bearing on the p- and νp-processes and on the site of the first peak of the r-process. The ejecta spatial distributions of both Ye and mass density are predominantly in wide-angle plumes and large-scale structures, but are nevertheless quite patchy.